O português como língua de heranca na percepção de adolescentes residentes no exterior: memórias, afetividade e questões de identidade - Lico, Ana Lucia Cury (2024)
Studies on programs that teach Portuguese to children of Brazilians living abroad, a field known as Portuguese as a heritage language, show that adolescents’ connection with their parents’ roots and native language tends to weaken as they grow up. Some of the possible consequences of this weakened connection with the parents’ home country are loss of their heritage language and culture, and a lack of belonging to their inherited identity. This research was born out of my interest in identifying ways to avoid or reverse this disconnection of adolescents from their heritage language and culture (HLC). The main goal of this work is to the understand the adolescents’ perspective on their journey of learning Portuguese as a heritage language (PHL), in relation to the level of connection they have with the Brazilian identity. The specific objectives are a. to identify whether there is an influence of the PHL learning process and path on the learner’s connection to the Brazilian identity; b. to analyze adolescents’ perceptions about the process of acquiring the Portuguese language since childhood and the construction of awareness in this language. The research context involves the learning path of two teenagers, who happen to be my sons, born and raised in the USA, and exposed to a bilingual and multicultural environment since they were born. As for the theoretical framework, I turned to authors with relevant work in the field, such as Flores (2015), Hall (2006), Ellis (2007), Montrul (2012), Wang (2015), Zhou and Liu (2023), among others. I chose narrative inquiry as the method, qualitative in nature, anchored in the theoretical-methodological perspective of Amado (2014), Barkhuizen (2015) e Barcelos (2020). The instruments used were individual semi-structured interviews and a round of conversation with the two teenagers. The assumptions that the concept of identity for learners of heritage language and culture is fluid, dynamic and results from the experiences and situations lived in the host country and that the acquisition of Portuguese as a heritage language by teenagers is trespassed by affectivity and intrinsically linked to the creation of opportunities for/by families to use the language are key for this research. Besides, it’s important to consider that, although there is a high rate of adolescents who, over the years, move further away from their origins, others keep close ties to their HLC. I hope this study will contribute to shed light upon critical issues regarding the transmission-acquisition process of PHL for adolescents in relation to the connection they establish with their cultural roots and inspire parents and educators to encourage them to continue (or resume) their language acquisition path.